75 YEARS OF MEPHI’S HISTORY: CONTINUITY OF EDUCATIONAL INNOVATIONS - I. E. Zadorozhnyuk (Высшее образование в России, 2018)
The monograph “Chronicles of Nuclear University MEPhI” (the authors – N.A. Kudryashov and M.N. Strikhanov) published in the series “Science in the Soviet Union: Through the difficulties to the stars” is devoted to the first 50 years of the history of MEPhI. The book focuses on the educational innovations characterizing Moscow Engineering Physics Institute, now – the National Research Nuclear University MEPhI as a center of scientific and technological development of the country. The key innovation inherent in its very basis is coupling of educational process with students’ research activities from the very first days of their stay at the University. This innovation is closely connected with a unique brand of MEPhI – so called “Career Time Compression” that is illustrated by the career of one of its rectors – V.G. Kirillov-Ugryumov. The book introduces into scientific circulation the archival materials, biographical data, the exclusive historical materials based on documentary evidences and memories of scientists of one of the best universities in the country. The authors convey the history of the legendary institution through the fate of people who took part in its formation.